Dosimetric effect of the gantry rotations of a novel trunk phantom using an area integration algorithm - Michael Onoriode Akpochafor; Akintayo Daniel Omojola; Muhammad Yaqub Habeebu; Samuel Olaolu Adeneye; C B Madu; M E Ekpo; Moses Adebayo Aweda; Temitope Aminat Orotoye (Journal of Medical Sciences, 2018)
Background: Treatment planning systems (TPSs) have proved to be a useful tool in predetermining how a treatment outcome will be in radiotherapy. The accuracy of any TPS to calculate dose to any arbitrary point within a material is largely dependent on the mathematical algorithm used. Aims: The purpose of this study was to design a local trunk phantom and use the phantom to check the percentage dose accuracy of the Area Integration Algorithm of a Precise PLAN 2.16 TPS if it is in agreement with results obtained from manufacturer's verification by varying the gantry angle and whether it is within ± 5% International Commission on Radiation Units and Measurements (ICRU) minimal limit. Materials and Methods: The study was executed with a locally designed phantom made of Plexiglas with six insert and an ionization chamber port. The phantom was simulated using a HiSpeed NX/i computed tomography scanner and Precise PLAN 2.16 TPS for application of beam setup parameters. The mimicked organs for the inserts were: 25%–75% Glycerol-Water for liver, pure carboxyl methyl cellulose was used for lungs, 30%–70% Glycerol-Water for muscle, 40%–60% Glycerol-Water was used for adipose, pure Sodium hypochlorite was used for bone and pure sodium laureth sulfate (Texapon) for kidney. Results: The maximum percentage (%) deviation with a large field for six inhomogeneous inserts and with bone only homogeneous inserts were 3.4% and 2.9%, respectively. The maximum % deviation with a small field for six inhomogeneous inserts was 3.2%. The % deviation between the solid water phantom and the locally designed phantom was 3.5%. Conclusion: The Area Integration Algorithm has shown an overall accuracy of 4% below 5% ICRU minimal limit. There was no statistically significant difference in field sizes and in inhomogeneity/homogeneity, respectively. Variation exists in % deviation for small field size with parallel opposed field between our verification and the manufacturers.